Fundamental British values in education : radicalisation, national identity and Britishness - Revell, Lynn; Bryan, Hazel (Emerald points., 2018)
This timely book provides a critical analysis of the statutory requirements to promote Fundamental British Values in educational settings in the UK. It explores British values as they appear in contemporary policy and legislation as well as how Britishness as a concept has evolved in relation to education in the post-war period.